1993
DOI: 10.1080/02640419308729962
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory threshold and work efficiency during exercise on a cycle and rowing ergometer

Abstract: The purpose of this investigation was to determine the effects of increasing specific (rowing ergometer) and non-specific (cycle ergometer) workloads on parameters relating to the ventilatory threshold (Tvent) and work efficiency. When highly trained male rowers were tested using non-specific workloads, their %VO2 max values at Tvent were close to those characteristic of untrained subjects (74.6 +/- 6.2% VO2 max). However, when we tested the same subjects using specific workloads, we recorded values typical of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
5
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(62 reference statements)
3
5
0
Order By: Relevance
“…Values of the V E time constant at approximately 59 seconds have been found during upper-limb exercise, with higher variability in moderate workloads than in heavy workloads (3). Although similar to other studies (1,5), it is possible that the workload increased-duration relationship used here has not allowed a complete V E response during each increase of workload, leading to delayed response of V E at each stage. As a consequence of delay, the first linearity break point of V E could be delayed, and, consequently, this would lead toward the second linearity break point, providing only 1 break point and making the Three-SEG fitting unsuccessful.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Values of the V E time constant at approximately 59 seconds have been found during upper-limb exercise, with higher variability in moderate workloads than in heavy workloads (3). Although similar to other studies (1,5), it is possible that the workload increased-duration relationship used here has not allowed a complete V E response during each increase of workload, leading to delayed response of V E at each stage. As a consequence of delay, the first linearity break point of V E could be delayed, and, consequently, this would lead toward the second linearity break point, providing only 1 break point and making the Three-SEG fitting unsuccessful.…”
Section: Discussionsupporting
confidence: 74%
“…Nevertheless, because the V E time constant depends on increased magnitude, it is unlikely that the V E behavior observed here would be different from the majority of studies that identified the ventilatory threshold of the V E curve during upper-body exercise (1,5). Therefore, it is possible that a best Bi-SEG fitting could also be found in previous studies, with only 1 ventilatory threshold identified.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…It is well known that the maximal oxygen uptake depends on the muscle mass recruited for exercise [12][13][14][15]. Similarly, some reports showed that 2 @VT during rowing or running was greater than that during a cycle ergometer exercise [7,8]. It is plausible that whole body exercises as compared with partial exercises yield higher values for aerobic parameters.…”
Section: Greatermentioning
confidence: 99%
“…Therefore, it would be expected that aerobic conditioning at the VT level during horizontal load walking would be safe and useful for an exercise prescription. In contrast, several studies have found that the VT differed between different modes of exercise [7,8]. Therefore, it was assumed that the VT of horizontal load walking could be characterized by comparing it with that of a cycle ergometer exercise.…”
Section: Introductionmentioning
confidence: 99%